Bukan Hanya Situs Berita: Ikhtisar dan Tren Jurnalisme Online Indonesia - Titis Nurwulan Suciati; Ratna Puspita (CoverAge: Journal of Strategic Communication, 2019)
Online journalism has evolved since nearly the last two decades to produce a variety of journalistic products that combine the culture of print journalism and new media technology. This research investigates the evolutionary trends in searching and presenting online news in Indonesia by considering the dynamics of convergence caused by the presence of the internet. Online journalism in Indonesia presents various models of presenting news by utilizing the web or website or pages and social media. The development of online journalism in Indonesia is not only demonstrated through the presence of news sites, but also the existence of feed reader pages or news aggregators. This change in online journalism practices in Indonesia poses challenges for lecturers who teach journalism specifically and communication science in general. This study aims to explain the concept of online journalism that applies in Indonesia. In this study, researchers will gather previous studies on online journalism in Indonesia to then describe the problems that arise in online journalism in Indonesia, the methods used to examine them, and data collection techniques. Researchers hope this research will be the initial stage of research on online journalism in Indonesia so that later there will be teaching modules for students of communication science in general and journalism in particular.